Hegel and Aristotle on Ethical Life: Duty-Bound Happiness and Determined Freedom. Issue 1 (April 2020) - Stein, Sebastian
Abstract: Hegel's account of ethical life can be shown to contradict Aristotle's in two main ways: first, Hegel follows Kant in emancipating virtue/duty from the particularity associated with the content of motivational drives and with Aristotle's eudaimonia . Hegel thus rejects Aristotelian happiness as the final end of rational action and prioritizes duty. However, against Kant, Hegel unites (1) abstract duty and (2) determined drives within a speculative notion of ethical duty: rational agents find happiness in heeding duty's call. Second, Hegel follows Kant in emancipating agency's subjective dimension from the all-encompassing determinacy of Aristotelian substance metaphysics. At the same time and against Kant, Hegel unifies agency's undetermined, subjective dimension with the determinacy of objective norms and habitual praxis: ethical praxis must be animated by undetermined subjectivity whilst being determined. In both cases, Hegel goes beyond Aristotle by resting his argument on the speculative structure of 'the concept of the will'.